Historical Redlining and Community-Reported Housing Quality: A Spatial Analysis: Historical Redlining and Contemporary Housing Quality: Milletich et al. - Milletich, Salvatore; Manrique, Andres; Karsan, Sonia; Spikes, Tamara; Nanavanti, Anuj; Bailey, Jared; Coker, Eric; Ekenga, Christine C. (Journal of Urban Health, 2025)
Historical redlining, a racially discriminatory practice implemented by the US government in the 1930s, has been associated with present-day environmental outcomes. However, there is limited research examining the relationship between historical redlining and contemporary housing quality. The objective of the present study was to investigate the relationship between historical redlining and contemporary housing quality in Atlanta, Georgia. Spatial patterns of housing code violation complaints from 2015 to 2019 were examined using point-pattern and spatial cluster analyses. We used Bayesian hierarchical models, accounting for spatial autocorrelation, to estimate associations between historical redlining and housing complaints, after adjusting for contemporary neighborhood characteristics, such as poverty, median structure age, vacant and renter-occupied properties, and residential racial segregation. A total of 48,626 housing code violation complaints were reported during the study period, including 6531 complaints deemed "hazardous." Historical redlining was a statistically significant predictor of housing complaints. We observed a 167% increased risk (IRR = 2.67, 95% confidence interval = 1.49, 4.77) of housing complaints for historically redlined neighborhoods compared to neighborhoods historically graded as "best" or "still desirable," after adjusting for neighborhood characteristics. Redlined neighborhoods also had an increased risk of "hazardous" housing complaints (IRR = 1.94, 95% confidence interval = 1.11, 3.40), after adjusting for contemporary neighborhood characteristics. Historically redlined neighborhoods exhibited disproportionately higher rates of housing code violation complaints. Spatial analysis of housing code violation complaints can provide insights into housing quality and inform interventions targeted at addressing the environmental legacy of structural racism.